Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Short-Term Psychodynamic Therapy on Cognitive Fusion and Obsessive-Compulsive Symptoms in Individuals with Obsessive-Compulsive Disorder - Hosseini, Seyed Adel; Nasri, Maryam; Dastgerdi , Reza (Health Nexus, 2025)
The aim of this study was to compare the effectiveness of cognitive-behavioral therapy (CBT) and short-term psychodynamic therapy (STPP) in reducing cognitive fusion and obsessive-compulsive symptoms in individuals with obsessive-compulsive disorder (OCD). This semi-experimental study employed a pretest-posttest design with a follow-up phase. The statistical population included individuals with OCD who sought treatment at all counseling and psychological service centers in Birjand from April to December 2023. Sixty participants were purposively selected based on Cohen’s table and were randomly assigned to two experimental groups and one control group. The first experimental group received 10 sessions of cognitive-behavioral therapy, while the second experimental group received 11 sessions of short-term psychodynamic therapy. The control group did not receive any intervention during this period. Data were collected using the Cognitive Fusion Questionnaire by Gillanders et al. (2010) and the Obsessive-Compulsive Scale by Hodgson and Rachman (1977) at three stages: pretest, posttest, and follow-up. Repeated measures ANOVA was used for data analysis. The results indicated that both cognitive-behavioral therapy and short-term psychodynamic therapy significantly reduced cognitive fusion and obsessive-compulsive symptoms at the posttest stage (p < .05), and the therapeutic effects were maintained after three months. However, no significant difference was observed between the effectiveness of cognitive-behavioral therapy and short-term psychodynamic therapy in reducing cognitive fusion and obsessive-compulsive symptoms in individuals with OCD (p > .05). Based on the findings, there is no difference in the effectiveness of cognitive-behavioral therapy and short-term psychodynamic therapy in addressing cognitive fusion and obsessive-compulsive symptoms in individuals with OCD. Both approaches can be used to reduce and manage cognitive fusion and obsessive-compulsive symptoms in affected individuals.